THE IMPORTANCE OF INTERDISCIPLINARY INTEGRATION IN THE MODERN EDUCATIONAL PROCESS - Nafasov Arslon Komilovich (Web of Journals Publishing, 2025)
The article discusses the need to ensure interdisciplinary integration to ensure the effectiveness of teaching history in secondary schools. At the same time, the need to ensure interdisciplinary integration is scientifically substantiated using various examples.
Keywords: Integration, efficiency, interdisciplinary connection, critical thinking, professional competence, cognitive, creative, cause-and-effect.